Visualizing Variability in Ceramic Micro-Curvature though Novel 3D Morphometric Mapping and Sliced Segmental Extraction. Issue 1 (3rd August 2022) - Loftus III, James Frances; Seguchi, Noriko
In recent years, two-dimensional (2D) outline-based morphometric analysis has begun to be the standard means of shape analysis in the study of ceramics. Despite the ever-increasing repertoire of three-dimensional (3D) ceramic data available to researchers, due to challenges in utilizing landmark-based geometric morphometrics on ceramics, many contemporary studies are forced to rely on 2D outlines, which account for only a small degree of shape variance. Consequently, notions of intra-vessel variance cannot be thoroughly extrapolated, and as such, important themes such as morphogenesis during the production process have not been thoroughly examined. By contrast, the present project utilizes a method derived from high-resolution 3D scans combining "morphometric mapping" and "sliced segmental extraction" to visualize previously unrecognized variability in the micro-curvature of full vessels. This method does not require homologous landmarks, but rather, employs a multistage approach that allows for several stages of analysis that can be adjusted to each given research project, and thus has the potential to elucidate idiosyncratic variability during the morphogenesis process.